2014
DOI: 10.1109/tifs.2013.2291326
|View full text |Cite
|
Sign up to set email alerts
|

Top-$k$ Query Result Completeness Verification in Tiered Sensor Networks

Abstract: Storage nodes are expected to be placed as an intermediate tier of large scale sensor networks for caching the collected sensor readings and responding to queries with benefits of power and storage saving for ordinary sensors. Nevertheless, an important issue is that the compromised storage node may not only cause the privacy problem, but also return fake/incomplete query results. We propose a simple yet effective dummy readingbased anonymization framework, under which the query result integrity can be guarant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Network worms were also considered, and CPN was used to reroute the users' traffic to avoid the infected nodes (Sakellari and Gelenbe [176], Sakellari, Hey, and Gelenbe [177]). Further research on network security can be found in (Gelenbe et al [87], Gorbil et al [151], Yu et al [185]). …”
Section: Autonomic Systems and Cognitive Packet Network (Cpns)mentioning
confidence: 99%
“…Network worms were also considered, and CPN was used to reroute the users' traffic to avoid the infected nodes (Sakellari and Gelenbe [176], Sakellari, Hey, and Gelenbe [177]). Further research on network security can be found in (Gelenbe et al [87], Gorbil et al [151], Yu et al [185]). …”
Section: Autonomic Systems and Cognitive Packet Network (Cpns)mentioning
confidence: 99%
“…On the other hand, the cloud can be benign but accidentally report incomplete data due to an unexpected misconfiguration/error. Here, inspired by our previous work [15], we propose a dummy reading-based compression framework, where a virtual line segment approach is proposed to reduce the communication overhead and at the same time keep the benefit of detecting data incompleteness, at the expense of increased computation burden on the RCU side. In particular, we propose verifiable, privacy-assured, and accurate signal collection (VPAA) by integrating the rdOPE scheme with the virtual line segment approach.…”
Section: Verifiable Privacy-assured and Accurate Signal Collectionmentioning
confidence: 99%
“…Two approaches carried forward in securing the data in the existing technology were additional evidence and cross check. Additional evidence [1] generates message digest to verify the data. The sender will message digest the data and send to the receiver.…”
Section: Existing Work On Data Securitymentioning
confidence: 99%
“…Brokers are responsible for taking the routing decisions and to direct client queries to the corresponding data servers. Adopting server-side access control for data confidentiality is not sufficient in the existing IBS [1] since adversary can still infer the details of the data which is getting transferred between the brokers. Hence the secure transfer mechanism needs to be implemented for the data communication across the brokers as well.…”
Section: Existing Work On Data Securitymentioning
confidence: 99%